2010
DOI: 10.1002/j.2161-0045.2010.tb00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Life and Work Values of Counselor Trainees: A National Survey

Abstract: This national web-based study used the Schwartz Value Survey (Schwartz, 1994) and Super's Work Values Inventory-Revised (Zytowski, n.d.) to identify general life and work value orientations of 674 female and male entry-level counselor trainees residing in 27 states. In general, trainees emphasized benevolence, self-direction, and achievement and the work values lifestyle, supervision, and achievement. Significant multivariate and univariate differences for age, gender, and program of study were found on both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 28 publications
1
22
0
1
Order By: Relevance
“…One e-mail reminder was sent and yielded an 8% response rate. Busacca, Beebe, and Toman (2010) surveyed graduate student members in two professional organizations and sent one reminder 30 days later, yielding a 14% response rate. The most effective methods for using online surveys for research are still being determined and seem to be somewhat dependent on the population.…”
Section: September 2012 • Volume 60mentioning
confidence: 99%
“…One e-mail reminder was sent and yielded an 8% response rate. Busacca, Beebe, and Toman (2010) surveyed graduate student members in two professional organizations and sent one reminder 30 days later, yielding a 14% response rate. The most effective methods for using online surveys for research are still being determined and seem to be somewhat dependent on the population.…”
Section: September 2012 • Volume 60mentioning
confidence: 99%
“…Cassar (2008) found that work values were affected by students' university faculty. However, Busacca et al (2010) and Van Ness et al (2010) found that work value scores were significantly different between practicing workers and trainees or students. Therefore, work experience also has some effect on work values.…”
Section: Discussionmentioning
confidence: 94%
“…The study also found different value patterns in men and women managers' work and personal lives, suggesting that value hierarchy varies by gender. Busacca, Beebe, and Toman (2010), in their study of entrylevel counselor trainees, also found gender differences in work values. Women valued supervision (having a supervisor who is fair and who recognizes employees' value), workplace (being able to have a job where safety is not a concern), and lifestyle (having a job that does not compete with one's personal time) more than men did.…”
Section: Demographic and Job Factorsmentioning
confidence: 87%